EUS-guided endoscopic internal drainage with lumen-apposing metal stent for symptomatic hepatic cysts: a case series (with video) - DʼErrico, Francesca; Derhy, Serge; Fazi, Maurizio; Memeo, Riccardo; Decembrino, Francesco; De Palma, Giovanni D.; Donatelli, Gianfranco (Endoscopy International Open, 2023)
Background and study aims Simple hepatic cysts (SHCs) are usually asymptomatic and detected incidentally. However, larger cysts may present with clinical signs and require treatment such as percutaneous aspiration or surgery with non negligeable rate of recurrence. We report a series of 13 consecutive patients who underwent EUS-guided lumen-apposing metal stent (LAMS) drainage of SHCs of the right and left liver.Patients and methods Nine men and four women, average age 71.9 years, underwent EUS-guided LAMS cyst drainage because of significant symptoms. At 1 month, LAMS was exchanged for a double pigtail stent (DPS), which was left in place for 3 months. Nine of the SHCs were located in the right liver and four in the left. The average diameter was 22.2 cm. Results Thirteen LAMS were successful delivered in all patients. However only 12 of 13 (92.3 %) remained in place. In one case, the LAMS slipped out immediately and was promptly removed and the cyst treated percutaneously. One of 12 patients experienced bleeding, which was treated conservatively. In seven patients, the LAMS was exchanged for a DPS; in the other five, it was successfully left in place until the patients died, given their comorbidities. At 10.5 months of follow-up, none of the SHCs had recurred. Conclusions EUS-guided LAMS drainage permits treatment of symptomatic SHCs without recurrence and with few adverse events. Comparative studies are needed to consider this approach as first intention.